Peran Pendidikan Politik dalam Membangun Sikap Demokratis Siswa melalui Organisasi Siswa Intra Sekolah di SMP Negeri 22 Semarang - Shalihudin, Farid; Hermanto, Fredy (Universitas Negeri Semarang, 2021)
This study aims to determine the school's efforts in building student democratic attitudes through OSIS at SMP Negeri 22 Semarang. The results showed that schools made an effort to provide an understanding of political education. The OSIS management has implemented the understanding of political education provided by the school and can be seen through its activities. The implementation of understanding political education in building democratic attitudes is still not optimal. The active participation of the OSIS management includes; (1) decision making, (2) implementation, (3) taking benefits, (4) evaluation, and (5) social attitudes. Meanwhile, the results of the analysis of the role of political education in building student democratic attitudes show that coaching seeks to build the awareness of the student council officials, motivation plays a role in problem-solving, and evaluation plays a role in knowing the shortcomings of the student council administrators.